PENGEMBANGAN E-KOMIK SEBAGAI MEDIA PEMBELAJARAN KEAMANAN JARINGAN MATERI KRIPTOGRAFI - admin, admin (CV. Hawari, 2023)
Technology advances do not always have a positive effect on interest reading and learning student. From the facts that are often encountered, indicates that there are many students who do not like learning network security caused by several factors. Problems in this study is how the qualifications and the response of students to education media e-comics in cryptographic material. This study aimed to get a description of the qualifications e-comics and get response from the students to e-comics in the learning network security cryptographic material. This research method use a method of development research ADDIE (Analysis, Design, Development, Implementation, Evaluation). Instrument data sources using a questionnaire. validation of this research involve materials validator and media validator. The subjects were 25 students of Information Technology Education 2013 Unesa. The results showed appraisement of qualication from the validator is 84.5%. Thus e-Comics media can be said to be Very Well worth as a education learning of students.